The experiences of adults with intellectual disability in the involvement of nursing care planning in health services. (7th July 2019) - Doody, Owen; Lyons, Rosemary; Ryan, Ruth
Accessible summary: Adults with intellectual disabilities and their families receiving services have plans for their care, education and social support. This occurs through meetings and results in a "care plan" or "plan of support." There are differences in nursing, educational and social care plans. At present, adults with intellectual disability have little involvement in nursing care planning. Involving adults with intellectual disability in nursing care planning is important, and there is a need to share and publish this involvement. Abstract: Background: Adults with intellectual disability should be involved in decision‐making about their care. However, little is known regarding their experience of engaging in care planning within health services. In a rapidly changing healthcare environment, the relevance and necessity of demonstrating care delivered and care outcomes is essential for all professionals and this review highlights the need for intellectual/learning disability nurses to prioritise disseminating this evidence beyond the practice environment. Materials and Methods: Integrative literature review informed by the approach of Whittemore and Knafl (2005). CINAHL, Scopus, Web of Science, PsyArticles, PsycInfo, MEDLINE, Cochrane Library, Embase and Academic Search Complete were searched for papers published between 01 January 2005 and 01 June 2017. Results: No study met the inclusion criteria for nursing care planning. However, through examining the literature that made it to the full‐text review stage, two key aspects were identified: exploring the relevance and categories of plans, and disseminating evidence of practice. Conclusion: This integrative review provides evidence that the experiences of adults with intellectual disability involvement in care planning within health services are absent within the literature. While guidance exists regarding involving adults with intellectual disability in planning their care, there is confusion, ambiguity and an interchangeable use of terms that makes it difficult to distinguish between nursing care plans, person‐centred plans, individual programme plan, individualised support plan, health action plans, personalised support plans and personalised plans.